Nurturing a global ecojustice consciousness among preservice teachers through critical place-based learning - Greer Burroughs; Marissa Bellino (Journal of Global Education and Research, 2024)
Global environmental challenges brought on by over-consumption, limited resources, and climate change will task teacher education programs to prepare teacher candidates with new paradigms in problem-solving, collaboration, and innovation. Skills such as collaborating across cultures and borders, thinking critically and creatively, reflecting on deeply embedded assumptions, and negotiating uncertainty will all be needed to surmount these challenges. EcoJustice education addresses these needs. When combined with critical place-based pedagogies, skills, and attitudes associated with global citizenship may also develop. Four preservice teachers participated in a research trip to Lesvos, Greece, to learn about and aid in the refugee crisis there. Participants documented their experiences via critical reflections and dialogues and analyzed these data. Findings suggest that through engagement in a critical place-based learning experience, preservice teachers challenged conceptions of their role as Americans and shifted towards a more global, EcoJustice consciousness.